EXPLORING BUSUU APPLICATION TO IMPROVE STUDENTS’ SPEAKING SKILL - Fitri Novia; Kiki Rizki Amelia; Rosita Wati (Universitas Islam Ogan Komering Ilir Kayuagung, 2024)
The study aimed to determine whether speaking achievement differed significantly between students who received instruction using the Busuu application and those who did not. Purposive sampling was used to gather the sample. 56 students made up the study's sample and were split into two groups using a coin flip: the experimental and control groups. Classes VIII.1 and VIII.3 represented the experimental and control groups. Data collection took place by oral examination. The data analysis was done using a t-test. An independent sample ttest revealed that the obtained value (7.939) was greater than the t-table (2.004). It was determined that there was a considerable difference in speaking achievement between the students taught using Busuu and those not, as seen by the rejection of H0 and acceptance of Ha. The Busuu application was an excellent medium to improve students' speaking skills